Prevalence and comorbidity of the ICD-11 and DSM-5 for PTSD caseness with previous diagnostic manuals among the Japanese population. Issue 1 (31st December 2020) - Oe, Misari; Ito, Masaya; Takebayashi, Yoshitake; Katayanagi, Akiko; Horikoshi, Masaru
ABSTRACT: Background : The diagnostic criteria for posttraumatic stress disorder (PTSD) differ between DSM-5 and ICD-11, which may affect the estimation of prevalence. Objective : To investigate the concordance of ICD-11 and DSM-5, as compared to ICD-10 and DSM-IV, regarding PTSD caseness among Japanese people who had experienced different potentially traumatic events. In addition, we estimated the comorbidity with major depressive disorder and generalized anxiety disorder according to these four diagnostic manuals. Method : A web-based survey ( n = 6, 180) was conducted from November 2016 to March 2017. Participants completed the PTSD Checklist for DSM-5, and other standardized measures of PTSD, depression, and anxiety. Results : The prevalence of PTSD caseness according to ICD-11 was significantly lower as compared to DSM-IV, DSM-5, and ICD-10. Cohen's kappa between DSM-5 and ICD-11 was 0.79, indicating substantial agreement. Comorbidity with depression was significantly higher in unique DSM-5 cases than in unique ICD-11 cases. Unique DSM-5 PTSD cases were significantly stronger functionally impaired than unique ICD-11 PTSD cases. Conclusions : Although requiring fewer items, the ICD-11 showed substantial agreement with DSM-5 regarding PTSD caseness. The lower comorbidity rates in unique cases may support the concept of the ICD-11 which intends to reduce comorbidity by identifying the core elements of PTSD.